2014
DOI: 10.5812/jjm.17460
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii in Cattle, Camels and Sheep in Isfahan and Chaharmahal va Bakhtiary Provinces, Iran

Abstract: BackgroundToxoplasma gondii is a zoonotic parasite, which is assumed to have cosmopolitan distribution.ObjectivesAdopting a cross-sectional study design the current research aimed to determine the occurrence of the parasite in cattle, camels and sheep in Isfahan and Chaharmahal va Bakhtiary provinces of Iran.Materials and MethodsAnimals in the field and those brought for slaughter at abattoirs were included. Blood samples were randomly collected from animals and investigated by polymerase chain reaction (PCR).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
4
13
0
Order By: Relevance
“…The investigations demonstrated that gender influenced the incidence, severity, and course of T. gondii infection especially in female mice with severe brain inflammation [60], and severe combined immunodeficiency [61], while enhanced innate immune responses were reported in males [62]. It is also showed that the gender-based difference in responses to T. gondii is due to hormonal profiles [51,54,57,63], and reduced females immunity due to nutrition [63,64], age [54,63], reproductive and certain environmental factors [7,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…The investigations demonstrated that gender influenced the incidence, severity, and course of T. gondii infection especially in female mice with severe brain inflammation [60], and severe combined immunodeficiency [61], while enhanced innate immune responses were reported in males [62]. It is also showed that the gender-based difference in responses to T. gondii is due to hormonal profiles [51,54,57,63], and reduced females immunity due to nutrition [63,64], age [54,63], reproductive and certain environmental factors [7,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…In 2011-2012, T. gondii was shown to be present in 3.12% of camel milk samples in Tehran, Isfahan and Fars provinces (Dehkordi, Barati, et al, 2013;Dehkordi, Haghighi Borujeni, et al, 2013). In 2013 and 2015, studies on T. gondii in camel blood samples showed that 6.6% and 65% of camels were infected in Isfahan and Khorasan Razavi provinces, respectively (Khamesipour Doosti, Mobarakeh, & Komba, 2014;Khamesipour, Rahimi, Shakerian, Doosti, & Momtaz, 2014;Sazmand & Joachim, 2017). Consumption of undercooked camel meat may constitute a risk of infection to humans and should, therefore, be of public concern.…”
Section: Toxoplasmosismentioning
confidence: 99%
“…According to these investigations, infection in cows was 0% in Mazanadaran in the north, 14.8% in Ahvaz in the southwest, 1.6% in Urmia, and 15.91% in Tabriz in the northwest of Iran. 17,[23][24][25][26][27][28] The prevalence of toxoplasmosis in the blood samples taken from the sheep in Isfahan and Chaharmahal and Bakhtiari provinces was determined to be 17.9 using the PCR method. Regarding the fact that the parasite is found in the acute phase of the disease in the blood, the chronic stages of the disease may have been ignored.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the discrepancy between the results of the present study and those of previous studies could be justified. 26 According to serological assessments, IFA with 95% sensitivity and 96% specificity is the most sensitive and specific method in diagnosing T. gondii in comparison with ELISA (enzyme linked immunosorbent), DAT (direct agglutination test), IHA (indirect hemagglutination assay), and LAT (latex agglutination test). 17…”
Section: Discussionmentioning
confidence: 99%